Conflict between pedestrian and ciclovia: a Avenue case study in Mandacarú Maringá - PR - Simoni, Julio Henrique; Fiorelli, Mariana Natale; Alencar, José Luciano Sobreira de; Neto, Generoso De Angelis (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The main objective of this article is to analyze critical points about a bike path at Mandacarú avenue in the Maringá city, PR and also their conflicting aspects with pedestrian which includes the quality of infrastructure of the path offered to users, public urban space circulation - sidewalks and short paths. To acquire data for this article was done observations in local, photographies as well as quick talk with the pedestrian about the situation of the path. Thus, according to the data acquired was possible to have an ideia about the accessibility, signage, security, its users, lighting and others aspects. Note that to validate that study all the methods were applied in the specific neighborhood in the Maringá city, PR which the beginning is at Colombo avenue and ending at the Rotatória das Torres - Torres avenue.